Capacity Enhancement Strategy - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
This is an outdated document for CCAFS Phase I. The Phase II Capacity Development strategy can be found here: http://hdl.handle.net/10568/82591. Capacity enhancement is a central priority for CCAFS. There is strong institutional support for this prioritization in the mandate of the ESSP, which has an explicit strategy agenda to make sure that capacity enhancement is more than just a tool for implementation of scientific research, and CGIAR, for which collaboration and capacity enhancement are likely to have a high profile within the post-reform agenda.